Turning the world upside down: a century of missionary endeavour - Echoes of Service; Stunt, William Thornburgh, 1909-; Pulleng, Alexander, 1897-; Pickering, Arnold, 1908-; Simmons, George Philip, 1901-; Boak, Donald Kenneth, 1930-; Warren, Stanley Francis, 1919- (Eastbourne, UK Upperton, 1972)
Includes indexes.
Copy 1 : Donated by Outreach Book Service : as an expression of fellowship in your work and ministry, 5.3.73. Copy 2 : Inscription reads : To Lando with seasons greetings from Rhoda, 1972.
Keywords: Brethren movement -- missions -- history